2014
DOI: 10.11113/mjfas.v10n2.262
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical study on chiral recognition mechanism of ketoconazole enantiomers using heptakis (2,3,6-tri-O-methyl)-β-cyclodextrin

Abstract: Capillary electrokinetic chromatography (EKC) has been established as a versatile and robust capillary electrophoresis (CE) method for the separation of enantiomers. One of the most attractive advantages of EKC for the separation of enantiomers is its ease of change of separation media in method development. The separation solution can easily be altered to find the optimum separation media and one can also use an expensive chiral selector because small amounts of it are required. This work aims to develop expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…This study found that the inclusion mechanism of TMβCD and ketoconazole is favored by the inclusion of a dichlorophenyl moiety and imidazole group towards the wider rim / secondary hydroxyl group of the TMβCD, which is correlated with our previous study, where we manually modeled the inclusion of the complexes. In our previous study, Model A, which is insertion of the dichlorophenyl moiety towards the wider rim of TMβCD, was found as the most favorable inclusion as compared with Model B.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…This study found that the inclusion mechanism of TMβCD and ketoconazole is favored by the inclusion of a dichlorophenyl moiety and imidazole group towards the wider rim / secondary hydroxyl group of the TMβCD, which is correlated with our previous study, where we manually modeled the inclusion of the complexes. In our previous study, Model A, which is insertion of the dichlorophenyl moiety towards the wider rim of TMβCD, was found as the most favorable inclusion as compared with Model B.…”
Section: Resultssupporting
confidence: 87%
“…However, to the best of our knowledge, the chiral recognition mechanism of the four enantiomers of ketoconazole on heptakis(2,3,6‐tri‐ O ‐methyl)‐β‐cyclodextrin (TMβCD) has not yet been reported thus far using docking studies. Our previous study discussed the theoretical studies of chiral recognition mechanism of ketoconazole using a different approach by manually placing the ketoconazole inside the CD cavity. However, it does not take other spatial arrangements into account.…”
mentioning
confidence: 99%
“…19 Enantioseparation by CE offers many advantages such as short analysis time, 3 little amount of chiral selector, analytes and buffer, and wide range of applications. 22 The selection of various chiral selectors that make CE an important and a versatile tool in enantioseparation have been previously reviewed, which include native and/or derivatized cyclodextrin (CD), protein, crown-ethers, chiral surfactants, metal-chiral amino acid complexes and macrocyclic antibiotics. 23 Among these, CD and their derivatives are the most popular chiral additives attributed to its characteristic such as high-resolution capability towards racemic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows (R)-miconazole and (S)-miconazole, as well as (2R, 4S)-ketoconazole and (2S, 4R)-ketoconazole. 22,25 Details about the antifungal and biological properties, pharmaceutical and toxicity profiles of both compounds remain insufficient due to limited amounts of pure individual enantiomers available for study. 26 Hence, to the knowledge of the literature, the performances of ketoconazole and miconazole are stereoselective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation